Tail shape classification of Tyrannus species based on geometric morphometrics - Fasanelli, Martín Nicolás (2021)
Tail morphologies of birds are driven by natural and sexual selection affecting flight performance, foraging strategies and even communication. These evolutionary processes fueled tail diversity but, until now, no study proposed a sound criterion to quantify and interpret such phenotypical variation. Tyrannus (Tyrannidae) is a New World group which includes 13 species with a wide range of tail morphologies, classically categorized into five shapes (round, square, notch, shallow fork and deep fork) based on the rectrices? length proportions. Although descriptive, we think this linear (and arbitrary) approach may not be enough to grasp forms and their conformational aspects. Our aim was to describe and quantify tail shapes of all the species in Tyrannus ? via geometric morphometrics ? in order to assess the clustering structure of the sample and the correspondence to their traditional categorizations. Tail shape of nondeep forked species (i.e., previously grouped with round, square, notch or shallow-fork tail) failed to display any clustering structure matching the traditional categorization, while deep-forked species were subdivided into two (morpho)groups. When model-based clustering was applied to the entire specimens distribution, eight different groups were detected, while combining and disengaging traditional tail categories. Our results showed that classic categories cannot be retrieved as consistent morphogroups. This lack of descriptive resolution indicates that the whole variability of Tyrannus? tail phenotypes could be not only underestimated but misinterpreted if preset categorizations are forcefully applied.